Implementasi Peraturan Bupati Padang Lawas Utara Nomor 24 Tahun 2023 dalam Penyelenggaraan Pilkades Perspektif Siyasah Dusturiyah : Studi Kasus Desa Ujung Batu Jae Kecamatan Ujung Batu) - Harahap, Fitriani; Harahap, Mhd. Yadi (STAINI Press, 2025)
The election of the Village Head (Pilkades) is a tangible form of democracy at the local level which should ideally be carried out honestly, fairly, and transparently. However, in its implementation, there are still many irregularities that hurt these democratic values. One of the crucial problems is the occurrence of fraud in the nomination stage of the village head. This study highlights the implementation of the North Padang Lawas Regent Regulation Number 24 of 2023 concerning Guidelines for the Implementation of the Regional Elections, especially in overcoming fraud that occurs in Ujung Batu Jae Village, Ujung Batu District, North Padang Lawas Regency. The fraud that occurs includes the practice of partisanship, injustice, nepotism, and collusion by the election committee, which is contrary to Article 11 paragraph (6) of the Perbup which requires the committee to be independent and impartial. This study uses an empirical legal approach with two analysis methods, namely the statute approach and the case study approach. Data were collected through primary sources (interviews, field observations) and secondary sources (legal documents and Islamic literature). The location of the study was centered in Ujung Batu Jae Village as a representation of cases of violation of regulations in the Pilkades. The research results show that the implementation of this Regent's Regulation has not been optimal. Of the 108 villages scheduled to hold simultaneous village head elections in North Padang Lawas Regency, 105 have completed the stages optimally. However, there are several villages, including Ujung Batu Jae Village, that have experienced serious obstacles due to strong indications of fraud at the nomination stage. The fraud found included the disenfranchisement of certain candidates, administrative manipulation, and the influence of kinship relationships in the committee structure. From the point of view of Siyasah Dusturiyah as part of the fiqh siyasah, violations of the basic principles of Islamic constitutionality were found, namely: 1) Amanah (al-amanah): The committee does not carry out its duties with full responsibility and neutrality. 2) Justice (al-'adl): Certain candidates are treated unequally, which harms the principles of public justice. 3) Public interest (al-maslahah al-'ammah): This fraud has a negative impact on social stability and creates conflicts in society.